Teaching religions in Indonesia Islamic Higher education: from comparative religion to Religious Studies - Media Zainul Bahri (IAIN Salatiga, 2014)
This article focuses on how the study of Comparative Religion conducted in Indonesian Islamic higher institutions, i.e. on both UIN Yogyakarta and Jakartasince the beginning of the New Order (1960s) to Reform era (2014). The focus of the study was on models/approaches and main issues. In general, for more than half a century, the comparative study of religion is not been done for academic purposes an sich. Just within the new last decade that theoretical studies of Comparative Religion began developed. Another important thing that the study of Comparative Religion in Indonesia, although mostly referring to the methodological sources of the West and the Middle East, but ithas always been associated with religious and cultural context of Indonesia.Therefore, the study on both UIN Yogyakarta and Jakarta always deliver courseson religions that live in Indonesia alongside with Indonesian contemporary issues. In the reform era, though still using Comparative Religion’s term, butit looks religious studies such as used in the West. Thus, its “form” or “clothes”is Comparative Religion but it is religious studies. Artikel ini fokus pada bagaimana studi Perbandingan Agama yang dilakukan di lembaga-lembaga pendidikan tinggi Islam Indonesia, yaitu pada UIN Yogyakarta dan Jakarta sejak awal Orde Baru (1960) Reformasi era (2014). Fokus penelitian adalah pada model/pendekatan dan isu-isu utama. Secara umum, selama lebih dari setengah abad, studi perbandingan agama tidak dilakukan untuk tujuan akademik an sich. Hanya dalam dekade terakhir studi teoritis Perbandingan Agama mulai dikembangkan. Hal lain yang penting bahwa studi Perbandingan Agama di Indonesia, meskipun sebagian besar mengacu padasumber-sumber metodologi Barat dan Timur Tengah, tetapi selalu dikaitkan dengan konteks agama dan budaya Indonesia. Oleh karena itu, penelitian pada kedua UIN Yogyakarta dan Jakarta selalu memberikan kursus tentang agamayang hidup di Indonesia bersama dengan isu-isu kontemporer Indonesia. Dalamera reformasi, meskipun masih menggunakan istilah Perbandingan Agama, tetapitampak sebagai religious studies seperti yang digunakan di Barat. Dengan demikian,“bentuk” atau “pakaian”nya adalah Perbandingan Agama bahkan religious studies.